Pyogenic lung abscess in an infectious disease unit: a 20-year retrospective study. (June 2021) - Maitre, Thomas; Ok, Vichita; Calin, Ruxandra; Lassel, Ludovic; Canestri, Ana; Denis, Michel; Hamidi, Mohammed; Tavolaro, Sebastian; Verdet, Charlotte; Parrot, Antoine; Cadranel, Jacques; Pialoux, Gilles
Background: Pyogenic lung abscesses are rare and poorly described infections. This study aimed to describe their prognostic factors. Methods: We retrospectively included all patients hospitalized between 1 January 1998 and 1 June 2018, with an International Classification of Diseases, version 10 (IDC-10) diagnosis of pyogenic lung abscess, from the Diamm based medical records (Micro6, Nancy, France). Parasitic, fungal, or mycobacterial lung abscesses were excluded. Results: A total of 64 patients were included. Abscesses were associated with immunosuppression in 28 patients, including HIV infection and immunosuppressive therapy for eight and 12 patients, respectively. Bacterial identification was obtained for 36 patients. Nine patients (14%) developed lung abscesses after hematogenous dissemination. They differed from bronchogenic abscesses by their younger age ( p  = 0.03), the absence of smoking or emphysema ( p  = 0.05), Staphylococcus aureus ( p  = 0.001) or Streptococcus spp. ( p  = 0.05) isolation, and the smaller size of their abscess ( p  = 0.02). Overall, evolution was marked by radiological sequelae (46.9%), relapse (12.5%), and death (4.8%). Radiological sequelae occurred more frequently during the course of bronchogenic abscesses ( p  = 0.02), particularly when they spontaneously discharged ( p  = 0.04). Relapses were more frequent in patients with emphysema ( p  = 0.04) and when Haemophilus influenzae was isolated ( p  = 0.04). In multivariate analysis, poor outcomes, including death, sequelae, and relapse occurred more frequently in patients who had bronchogenic abscess ( p  = 0.02), and in those who received antibiotics during less than 6 weeks ( p  = 0.05). Conclusion: A duration of antibiotic treatment of less than 6 weeks and bronchogenic presentation were globally associated with poor outcome of pyogenic lung abscesses. These data should be considered when proposing guidelines for the care of pyogenic lung abscesses. The reviews of this paper are available via the supplemental material section .